The Role of Medical Imaging in the diagnosis of COVID-19 pneumonia - Silva, Sara (2020)
This study comprises a literature review with the objective of demonstrating the value of medical imaging in the diagnosis of COVID-19. It presents particular imagiological characteristics of pneumonia which suggest infection by the new Coronavirus or something else. SARS-CoV-2 is a new virus of unknown origin that emerged in December 2019 in China. The diagnosis is done through the Reverse Transcription Polymerase Chain Reaction (RT-PCR) laboratory technique. Imaging exams play a central part in assisting the diagnosis, monitoring and evaluation of the extension of lesions associated with the COVID19 pneumonia. Chest radiography shows low sensitivity and specificity in the diagnosis of COVID19, while the computed tomography (CT) shows high sensitivity in detecting pulmonary lesions, but low specificity. Imagiologically, this pathology follows a characteristic pattern similar to other viral pneumonias. However, recognizing the value of medical imaging on the diagnosis of COVID-19 pneumonia, the RT-PCR laboratory technique remains the most reliable.